Bioethanol production from cassava stem and peel: enzymatic hydrolysis, process optimization and fermentation performance - Vargas Gonzalez, Maria José (2025)
Cassava residues consist mainly of stems generated during harvest and peels produced during root processing. The stem is a lignocellulosic biomass, and the peel is rich in starch; both can serve as alternative carbohydrate sources for bioethanol production. Two central composite design (CCD) experiments were conducted in this study. In the first, cassava stem underwent sequential acid and alkali pretreatment to enhance cellulose accessibility. The aim was to optimize solid loading (SL) and protein loading (PL) for enzymatic hydrolysis to maximize glucose concentration (GC) and hydrolysis yield (HY). Optimal conditions of 174.44 g L−1 cellulose and 25 mg protein g−1 yielded a GC of 116.89±2.33 g L−1 and an HY of 80.19±1.61%. The second CCD optimized the enzymatic hydrolysis of cassava peel. Optimal parameters were 500 g L−1 solids, 40 μL g−1 solid α-amylase enzyme loading (AEL), and 30.7 μL g−1 solid glucoamylase enzyme loading (GEL), resulting in a GC of 211.60±5.74 g L−1 and an HY of 61.10±1.66%. Fermentation of the combined hydrolysates from cassava stem and peel produced an ethanol concentration of 103.74 g L−1, with a process efficiency of 92.2% and a volumetric productivity of 2.21 g L−1 h−1. © 2025 Society of Industrial Chemistry and John Wiley & Sons Ltd.